Given:
The equation is
[tex]y=-1(x-4.5)^2+15.25[/tex]
To find:
The standard form of the given equation.
Solution:
We have,
[tex]y=-1(x-4.5)^2+15.25[/tex]
It is a quadratic equation.
The standard form of a quadratic equation is [tex]y=ax^2+bx+c[/tex]. So, we need to write the given equation in this form.
[tex]y=-(x-4.5)^2+15.25[/tex]
[tex]y=-[x^2-2(x)(4.5)+(-4.5)^2]+15.25[/tex] [tex][\because (a-b)^2=a^2-2ab+b^2][/tex]
[tex]y=-[x^2-9x+20.25]+15.25[/tex]
[tex]y=-x^2+9x-20.25+15.25[/tex]
[tex]y=-x^2+9x-5[/tex]
Therefore, the required equation in standard form is [tex]y=-x^2+9x-5[/tex].